Essays on fuel policies in Brazil - Maxir, Henrique dos Santos (2020)
The Brazilian fuel market is an interesting case study. There are several policies regarding biofuels and fossil fuels. Since 1997, through Law No. 9,478 the called Oil Law, the oil industry permits the entry of foreign companies. In 2004, the establishment of the National Biodiesel Production and Use Program (PNPB) by Law No. 11,097 introduced the blend mandate of biodiesel in petroleum diesel. In 2017, Petrobras started a new pricing policy, frequently adjusting the fossil fuel prices and following the international level. In the same year, the government approved Law No. 13,576, creating the National Biofuel Policy (RenovaBio), which aims to reduce greenhouse gas (GHG) emissions with actions to expand biofuel production. The blend mandates of anhydrous ethanol in gasoline and between biodiesel and diesel play an important role since these policies combine fuel and food sectors such as sugar and soybeans. Thus, this thesis aims to evaluate complementary themes concerning fuel markets in Brazil through three essays. The first paper analyzes the oil industry between December 2002 and June 2017. We employ the New Empirical Industrial Organization (NEIO) model to assess demand and supply functions and the market power degree. The results show that the Brazilian oil industry is characterized as a monopoly in the analyzed period. The second paper examines the relationships between soybeans, biodiesel, and blended diesel (diesel C) sectors using data from January 2006 to December 2018. We use unrestricted and structural specifications of Vector Error Correction Models (VECMs) to evaluate: the linkages between prices of products of the soybean complex such as soybean grains, soybean meal, soybean oil, and biodiesel; the relationships between diesel, biodiesel, and soybean markets; and the demand for blended diesel. The estimates show that soybean prices from different locations in Brazil are important to determine the blended diesel price. An increase of 1% in petroleum diesel price impacts the diesel C price by 0.31-0.33%, while an equivalent expansion in biodiesel price decreases diesel C price by 0.22%-0.54%. The third paper measures the effects of several fuel policies on social welfare and GHG emissions. Through a partial equilibrium model concerning the sectors of gasoline, ethanol, biodiesel, diesel, other petroleum products, soybeans, and sugar, we evaluate different scenarios: Status Quo* adopts current fuel policies; First-Best scenario assumes a competitive market and GHG emission tax applied by the government; and, RenovaBio policy combines the existing policies and carbon credits supplied by biofuel producers and purchased by fossil fuel industry. The First-Best policy results in the highest surplus with a welfare gain of 40.40% and -11.49% of GHG emissions if compared to Status Quo*. The RenovaBio scenario produces -7.06% of GHG emissions, while welfare rises 0.31%, a gain of R$ 6.43 billion in the Brazilian economy.